Women and Global South strikingly underrepresented among top‐publishing ecologists. Issue 4 (1st March 2021) - Maas, Bea; Pakeman, Robin J; Godet, Laurent; Smith, Linnea; Devictor, Vincent; Primack, Richard
Abstract: The global scientific community has become increasingly diverse over recent decades, but is this ongoing development also reflected among top‐publishing authors and potential scientific leaders? We surveyed 13 leading journals in ecology, evolution, and conservation to investigate the diversity of the 100 top‐publishing authors in each journal between 1945 and 2019. Out of 1051 individual top‐publishing authors, only 11% are women. The United States, the United Kingdom, Australia, Germany, and Canada account for more than 75% of top‐publishing authors, while countries of the Global South (as well as Russia, Japan, and South Korea) were strikingly underrepresented. The number of top‐publishing authors who are women and/or are from the Global South is increasing only slowly over time. We outline transformative actions that scientific communities can take to enhance diversity, equity and inclusion at author, leadership, and society level. The resulting promotion of scientific innovation and productivity is essential for the development of global solutions in conservation science.